Hello Brand, let’s take a selfie - Uzunboylu, Naziyet; Melanthiou, Yioula; Papasolomou-Doukakis, Ioanna (My University, 2020)
Purpose: It has been suggested that brands and products often assume a role in selfies (Ham, 2014) where the expression of brands and products provokes consumer emotions that bring about greater engagement (Tsai and Men, 2013) and contributes to the interactivity with the brands. This study aims to understand how the selfie phenomenon could mobilize the interactivity between brands and target audiences, in a way that could be used as a marketing tool by companies. Design/methodology/approach: A netnographic research methodology was used for the current study because it is a method specifically designed to study online communities (Kozinets, 2010). The experiences of brand selfie postings on Instagram were studied by analyzing users’ selfies to predict brand usage. A purposive sample of Instagram users was chosen, and from these, a total of 74 brand selfies were analyzed. Findings: This study provided an understanding of consumer behavior and marketing practices in the social marketplace through a detailed exploration of the data using visual and textual analysis. The main finding of this study is that consumers both consume and produce brand meanings in digital platforms; hence, companies should view them not only as passive receivers of messages, but also potential generators and co-creators of brand messages. Research limitations/implications: An important limitation of this study is that it only examines a small number of cases, and conclusions can only be limited to the specific sample chosen. A future research endeavor could of course be carried out to include a larger sample audience for investigating the effect of brand selfies and the potential purchase decisions of peers following exposure. Theoretically, this study provided further insight into the selfie phenomenon and specifically as a marketing tool and not just a new social trend. Originality/value: The growing trend in the selfie phenomenon along with social networking sites (hereinafter SNSs) have attracted the attention of both users and marketing experts in terms of consumer–brand relationship (Zhu and Chen, 2015). In line with this current trend, many studies have attempted to understand the influential impact of the selfie phenomenon through SNSs. Studies on the motivation of selfie postings (Pounders et al., 2016) and selfie-posting behavior on SNSs (Kim et al., 2016) have been carried out; however, how brand selfies posted on SNSs appeal to non-users and how they interact with them remain unclear. Consequently, the intention of the current study is to provide some insight in this area.
Keywords: Branding; Selfie phenomenon; Netnography; Consumer relationships; Social media